Thioredoxin Ameliorates Cutaneous Inflammation by Regulating the Epithelial Production and Release of Pro-Inflammatory Cytokines - Tian, Hai; matsuo, yoshiyuki; fukunaga, atsushi; ono, ryusuke; nishigori, chikako; yodoi, junji (Frontiers in Immunology, 2013)
Human thioredoxin-1 (TRX) is a 12-kDa protein with redox-active dithiol in the active site -Cys-Gly-Pro-Cys-. It has been demonstrated that systemic administration and transgenic overexpression of TRX ameliorate inflammation in various animal models, but its anti-inflammatory mechanism is not well characterized. We investigated the anti-inflammatory effects of topically applied recombinant human TRX (rhTRX) in a murine irritant contact dermatitis (ICD) induced by croton oil. Topically applied rhTRX was distributed only in the skin tissues under both non-inflammatory and inflammatory conditions, and significantly suppressed the inflammatory response by inhibiting the production of cytokines and chemokines, such as TNF-α, Il-1β, IL-6, CXCL-1, and MCP-1. In an in vitro study, rhTRX also significantly inhibited the formation of cytokines and chemokines produced by keratinocytes after exposure to croton oil and phorbol 12-myristate 13-acetate. These results indicate that TRX prevents skin inflammation via the inhibition of local formation of inflammatory cytokines and chemokines. As a promising new approach, local application of TRX may be useful for the treatment of various skin and mucosal inflammatory disorders.